Impact of spam advertisement through e-mail: A study to assess the influence of the anti-spam on the e-mail marketing - Raad, M.; Yeassen, N.M.; Alam, G.M.; Zaidan, B.B.; Zaidan, A.A. (Academic Journals, 2010)
Several companies suffered from considering their e-mail advertisements as a spam. While others advertising those companies by employing spam technique to advertize the products, which makes an abusive use of the e-mails of users. In general, spam system classify the e-mails into wanted and unwanted massages, wanted massages are found in the inbox of the e-mails, while the unwanted massages are directed to the spam box. In many cases, anti-spams have several wrong estimations, although, the great roll of the anti-spam systems in term of privacy, security and protecting e-mails from any attacking cannot be ignored. From another view, spam cost the companies too much by assuming the advertisement massages as spam. Recently, most of the researchers are suffering from the spam false estimations; they tried to move toward approaches that minimizes the false positive estimations. In the literature, spam false estimations are considered as the main problem on e-mail marketing service (EMS). In this work we will illustrate the problems by investigating e-mail marketing service with many companies. In this paper also, we will describe the impact of the anti-spam on the e-mail marketing system by surveying the expert on the area of marketing. We analyze every single question with more than 70 specialists on marketing and their opinions have been recorded and analyzed in this paper. The analysis of the data shows anti-spam has directly affected the e-mail marketing services.